The Role of Pentecostal Worship in Virtues Development - Agustinus Dermawan (Jurnal Teologi Amreta (ISSN: 2599-3100), 2023)
As the readers may already knew, this author grew up in Pentecostal tradition, and I know that one of the primary characteristics of Pentecostalism is worship. I agree with what Robert Mapes Anderson said, "The heart of Pentecostalism is the worship service." In the same sense, Daniel Albrecht strongly believes too that the Pentecostal service lies at the heart of the Pentecostal/Charismatic spirituality. The fact that how important is worship in Pentecostal tradition draws my attention. It makes me to raise a question, "How significant is worship in the Pentecostal community?" or let me put it in more active question, "What is the role of Pentecostal worship in community?"